Pharmacokinetics and target animal safety of meloxicam and persistence of xylazine and ketamine after rendering in cattle - Fritz, Scott Andrew (My University, 2025)
Pharmacologic pain control in food animals undergoing normal management procedures is a recent focus in food production in the United States. Currently, there is only one analgesic drug that is FDA-approved for pain control; however, this drug is limited to control pain only associated with infectious pododermatitis in dairy cattle. Veterinarians can legally prescribe drugs to control pain in food animals for pain associated with other conditions or management procedures under the guidance of the Animal Medicinal Drug Use Clarification Act provided the mandates of that act are met. The lack of FDA-approval for pain control labels on analgesic drugs in food animals can largely be attributed to the difficulty in assessing pain in these species which contributes to variable reports in efficacy studies. Another significant hurdle in achieving regulatory approval is investigations into the safety of these drugs. Meloxicam is a non-steroidal anti-inflammatory drug often selected to control pain associated with painful management procedures in cattle. Adverse effects associated with oral meloxicam administration in other species include damage to the gastric mucosa, hypoxic kidney damage, and potential negative effects on the liver and bone marrow. Oral meloxicam dosed at 1 mg/kg bodyweight is approved to control pain in cattle in Canada. In this dissertation, the pharmacokinetics, milk concentrations, and safety of a single dose of meloxicam thirty times the magnitude of the Canadian product were evaluated in lactating dairy cattle. Drug concentrations were determined using high-pressure liquid chromatography coupled with mass spectroscopy. Pharmacokinetic parameters were modeled with non-compartmental methods using a commercially-available computational software. The potential adverse effects of this dose were monitored with ante-mortem testing using complete blood counts, serum chemistry analyses, urinalysis, and fecal evaluations. These animals were euthanized, and post-mortem evaluation included descriptions of gross lesions and histologic evaluation of potential target tissues. There was no impact on absorption of the large dose and maximum concentrations in serum and milk were approximately thirty and eighty times higher than those reported for 1 mg/kg oral doses with similar half-lives, respectively. There were no identifiable changes in blood parameters, urinalysis, or fecal evaluations from baseline. There were also no effects noted at necropsy and the study population tolerated the large dose well for ten days following administration. A target animal safety study was conducted in Holstein calves between 6 and 10 weeks of age. This study was modeled using FDA guidance documents on study design and outcome measures. The 1 mg/kg dose was used to calculate 3x and 5x doses and these were administered for three consecutive days. Serum drug concentrations were measured daily, and blood parameters were utilized for antemortem organ function monitoring. Calves were euthanized at multiple time points and gross and histologic lesions were described. There was a treatment-associated effect on gastric ulceration with the increasing doses which has not been previously described in cattle. Overall, the effects were clinically minor and unidentifiable via antemortem testing. This work may pave the way for evaluations of targeted analgesic regimens that may prove more effective for controlling pain. Xylazine and ketamine are two anesthetic drugs that may be used during the euthanasia process of food animals. Sodium pentobarbital was used previously but significant environmental concerns exist regarding its persistence following use. There have also been reports of pentobarbital contaminating pet foods as it survives the rendering process. Xylazine and ketamine were administered to cattle as part of the euthanasia process and samples of liver, kidney, fat, and muscle were collected. Concentrations of both drugs were determined in the raw tissues. The tissues were then exposed to a simulated rendering process using a commercial autoclave. Drug concentrations were determined in the rendered tissue and both drugs appear to persist through rendering. The concentrations detected after administration were relatively low and unlikely to pose a risk to pet foods. Future studies related to this work hinge upon the development of validated pain assessment techniques that regulatory bodies will recognize. Meloxicam is well-tolerated by cattle and studies evaluating the timing of different dose magnitudes could demonstrate increased effectiveness compared to the 1 mg/kg dose used in cattle in Canada. There are established limits of xylazine and ketamine in animal products meant for human consumption. Future work should focus on determining oral doses causing sedation and the associated concentration in pet food which may allow animals administered these drugs as part of the euthanasia process to be used for rendering capturing a valuable revenue stream for producers while minimizing the risk for adverse effects in animals consuming these products.
Keywords: Meloxicam; Safety; Toxicology; Residues; Cattle; Xylazine; Ketamine